Are N‐substituted glycine N‐thiocarboxyanhydride monomers really hard to polymerize?. Issue 3 (27th October 2016) - Tao, Xinfeng; Zheng, Botuo; Kricheldorf, Hans R.; Ling, Jun
ABSTRACT: N ‐Substituted glycine N ‐thiocarboxyanhydrides (NNTAs) are promising cyclic monomers to synthesize polypeptoids with the advantages of easier preparation and higher stability during purification and storage than N ‐substituted glycine N ‐carboxyanhydrides (NNCAs). NNTAs were commonly considered too stable to polymerize for their low reactivity. In this contribution, we report controlled polymerizations of N ‐ethylglycine NTA (NEG‐NTA) and sarcosine NTA (Sar‐NTA) using primary amines as initiator under proper polymerization conditions. The controllability has been fully supported by 1 H NMR end group analyses, MALDI‐ToF mass spectra, kinetic data, block copolymerizations by sequential monomer addition, and low polydispersities (1.14–1.17) of polypeptoids. Variation of the [NNTA]/[initiator] ratio allows well control of the molar mass, and degrees of polymerization (DPs) up to 287 can be reached for poly( N ‐ethylglycine) or DPs up to 262 for polysarcosine. NNTAs exhibit excellent activity and they are potential to synthesize polypeptoids with controllable polymerization. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 404–410 Abstract : N ‐Substituted glycine N ‐thiocarboxyanhydrides (NNTAs), alternative monomers for preparing polypeptoids, are easily accessible and stable during purification and storage, differing from N ‐carboxyanhydride (NCA) analogues that require extremely anhydrous and anaerobic conditions in synthesis. NTAs are commonly considered too stable to polymerize for their low reactivity. In this contribution, we report controlled polymerizations of NNTAs initiated by primary amines under proper solvents and high temperature to synthesis of well‐defined homo‐ and block‐polypeptoids.